2017
DOI: 10.1016/j.eats.2017.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Rotator Cuff Tears at the Musculotendinous Junction: Classification and Surgical Options for Repair and Reconstruction

Abstract: Although uncommon, rotator cuff tears that occur medially at the musculotendinous junction can result from acute trauma, anatomic force imbalance, or medial row cuff failure following a previous rotator cuff repair. The quality of the torn muscle and tendon along with the length of the remnant tendon stump should be considered before deciding on the most appropriate repair technique. When muscle and tendon quality are sufficient, the tear can often be repaired directly to the remnant tendon stump and compresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 48 publications
(77 reference statements)
0
19
0
Order By: Relevance
“…Type 2 repair failure can be related to poor shoulder function, pain, and impingement. 19 Moreover, revision surgery of type 2 retears might be technically challenging 1 because of the small amount of remaining tendon stock for repair. Therefore, the knot-tying SB RCR technique might result in serious clinical difficulties by causing strangulation of medial rotator cuff tissue, impairing vascular flow, and consequently causing necrosis of the rotator cuff and medial repair failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type 2 repair failure can be related to poor shoulder function, pain, and impingement. 19 Moreover, revision surgery of type 2 retears might be technically challenging 1 because of the small amount of remaining tendon stock for repair. Therefore, the knot-tying SB RCR technique might result in serious clinical difficulties by causing strangulation of medial rotator cuff tissue, impairing vascular flow, and consequently causing necrosis of the rotator cuff and medial repair failure.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5]31 Type 2 (medial) retears can cause impingement and are associated with pain and lower shoulder function and quality of life. 19,30 Moreover, revision of type 2 failure is more challenging. 1 Therefore, an SB RCR technique that uses knotless medial-row anchors has been developed to avoid overtensioning of the suture-tendon junction at the medial row and improve vascular inflow.…”
mentioning
confidence: 99%
“…6,25,49,50 This indicates that the tendon itself also needs to go through postoperative recovery. 24,36 The musculotendinous changes during the recovery process, such as inflammation, tendinitis, or preexisting tendinosis, might be related to pain, dysfunction, and potential failure of healing after RCR. 5,20,32,54 Magnetic resonance imaging (MRI) is widely used for evaluating tendon structural integrity and musculotendinous changes.…”
mentioning
confidence: 99%
“…Type 2 failures can cause impingement, severe pain, and devastating effects on shoulder function and quality of life. 19 The results of this study also indicated that shoulders with type 2 failure had inferior outcomes compared with shoulders with successful repair or type 1 failure, although the differences in the clinical scores were relatively small. Considering the difficulties of revision surgery for type 2 failures in addition to the effect on symptoms and function, it is important for surgeons to elaborate on repair techniques to decrease type 2 failure.…”
Section: Discussionmentioning
confidence: 55%